Non-SUMOylated alternative spliced isoforms of alpha-synuclein are more aggregation-prone and toxic. (January 2023) - Hassanzadeh, Kambiz; Morrone, Castrese; Akhtari, Keivan; Gerhardt, Ellen; Zaccagnini, Ludovica; Outeiro, Tiago Fleming; Feligioni, Marco
Abstract: The exon skipping of α-Synuclein (α-Syn), the main constituent of the abnormal protein aggregation in Lewy bodies of Parkinson's disease (PD), forms four isoforms. In contrast to the full length α-Syn (α-Syn 140), little is known about the splice isoforms' properties and functions. SUMOylation, a post-translational modification, regulates α-Syn function, aggregation, and degradation, but information about α-Syn isoforms and the effect of SUMOylation on them is unknown. Therefore, this study aims to characterize the SUMOylation of α-Syn isoforms and its impact on cell death and α-Syn aggregation. In a cellular model of PD induced by rotenone, cell toxicity, SUMOylation, and α-Syn aggregation with or without isoforms overexpression were evaluated. First, rotenone induced cell toxicity and α-Syn aggregation, with a significant reduction of SUMOylation and autophagy. Boosting SUMOylation prevented α-Syn aggregation, phosphorylation and recovery of autophagy. Moreover, α-Syn 140 and α-Syn 126 were SUMOylated while the other two isoforms, α-Syn 112 and 98 were not and their overexpression showed that were more toxic and induced more α-Syn aggregation. Rotenone increased their toxicity that was not affected by boosting SUMOylation. These results may indicate a role of SUMOylation in modulating α-Syn aggregation, inducing to understanding more about the behavior of α-Syn isoforms. Graphical Abstract: ga1 Highlights: Rotenone induces a PD-like cellular model, altering the apoptotic pathway, autophagy and SUMOylation and inducing α-Syn aggregation. Boosting the SUMOylation prevented rotenone-induced autophagy deficiency and α-synuclein aggregation. α-synuclein alternative splicing isoforms lacking exon 5, are not SUMOylated. Isoforms lacking exon5, are more toxic in the presence of rotenone and the induction of SUMOylation does not affect their toxicity. Isoforms lacking exon5, are more aggregated and increasing the SUMOylation does not affect their behavior.